Bangladesh’s agrifood system structure and drivers of transformation - Diao, Xinshen; Ellis, Mia; Pauw, Karl; Pradesha, Angga; Randriamamonjy, Josee; Thurlow, James (International Food Policy Research Institute, 2023)
Bangladesh experienced strong annual economic growth of 6.6 percent between 2009 and 2019 (BBS 2021). While the global COVID-19 pandemic caused a significant growth slowdown in 2020, growth started to recover in 2021. However, the recovery was hampered by global commodity market disruptions related to the war in Ukraine beginning in 2022 and the global recession in 2023 (Arndt et al. 2023; Diao and Thurlow 2023). The World Bank (2023) projects growth of 5.2 percent for 2023 and 6.2 percent for 2024, which is slower than the country’s pre-pandemic growth rate. Rapid growth in the past has already led to significant structural shifts in Bangladesh’s economy along with a transformation within the agrifood system (AFS). In this brief, we unpack these trends and future projections further to understand how Bangladesh’s AFS is contributing to growth and transformation in the country.